Making sense of Wnt signaling—linking hair cell regeneration to development - Jansson, Lina; Kim, Grace S.; Cheng, Alan G. (Frontiers in Cellular Neuroscience, 2015)
Wnt signaling is a highly conserved pathway crucial for development and homeostasis of multicellular organisms. Secreted Wnt ligands bind Frizzled receptors to regulate diverse processes such as axis patterning, cell division, and cell fate specification. They also serve to govern self-renewal of somatic stem cells in several adult tissues. The complexity of the pathway can be attributed to the myriad of Wnt and Frizzled combinations as well as its diverse context-dependent functions. In the developing mouse inner ear, Wnt signaling plays diverse roles, including specification of the otic placode and patterning of the otic vesicle. At later stages, its activity governs sensory hair cell specification, cell cycle regulation, and hair cell orientation. In regenerating sensory organs from non-mammalian species, Wnt signaling can also regulate the extent of proliferative hair cell regeneration. This review describes the current knowledge of the roles of Wnt signaling and Wnt-responsive cells in hair cell development and regeneration. We also discuss possible future directions and the potential application and limitation of Wnt signaling in augmenting hair cell regeneration.